Kewajiban Dakwah bagi Umat Muslim sebagai Peluang Diseminasi Ajaran Islam di Era Society 5.0 - Chotimah, Salsha Ainur (Maliki Interdisciplinary Journal, 2024)
The obligation of preaching to Muslims in the era of Society 5.0 is interesting to study. Because in this era, people are confronted by two roads. Where on the one hand, as Muslim human beings, society has an obligation to invite kindness to fellow humans as well as humans, making the presence of da’wah as a handheld tool necessary in the face of today’s globalizing world. In addition, in this era, people are also required to be able to keep up with the times according to the changes that exist. This means that people must have advanced and capable in terms of science and technology. In the era of society 5.0, people have been faced with various changes in which they must have the ability to adapt to changing times that are increasingly challenging. So that from the changes that have occurred, the community must also adapt and adjust in terms of habits, lifestyles, and so on which of course remain within the lines of religious law. So that the obligation of da’wah for Muslims in this era of digitalization is urgently needed as a guide and balancer for the revolution of the era that continues to develop.